1972
DOI: 10.1128/aem.23.1.170-171.1972
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Observations on the Uptake of Poliovirus by West Coast Shore Crabs

Abstract: West Coast shore crabs (Pachygrapsus sp. and Hemigrapsus sp.), when in seawater contaminated with poliovirus or allowed to feed on virus-contaminated mussels (Mytilus californianus), were found to accumulate high titers of virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…We have previously reported that West Coast shore crabs accumulate a considerable level of at least one enterovirus, type 1 poliovirus (3). Thus, we observed that Pachygrapsus sp.…”
Section: Uptake Of Bacteriophage By Edible Crabsmentioning
confidence: 53%
See 1 more Smart Citation
“…We have previously reported that West Coast shore crabs accumulate a considerable level of at least one enterovirus, type 1 poliovirus (3). Thus, we observed that Pachygrapsus sp.…”
Section: Uptake Of Bacteriophage By Edible Crabsmentioning
confidence: 53%
“…It has been well proven that bivalved molluscs (oysters, mussels, and clams) when harvested from sewage polluted waters, even if later cooked, could serve as vectors of viraldisease, e.g., infectious hepatitis (2, 5,6,8,9,10). Recently, it has also been shown that not only these shellfish, but also certain species of crabs, can become contaminated with virus, either from feeding off of contaminated shellfish or as a direct result of residing in sewagepolluted waters (3). However, the actual sites of virus accumulation within these animals is unknown, as is the extent of the hazard presented by the possible survival of virus in edible crabs after processing.…”
mentioning
confidence: 99%
“…Even crabs caught in unpolluted waters may be contaminated with viruses accumulated when the crabs were exposed to polluted waters, either by swimming and/or feeding on contaminated shellfish in polluted waters [191]. In laboratory studies, DiGirolamo et al [192] found that crabs concentrated high titers of poliovirus from contaminated mussels and filtered sea water that had been artificially seeded.…”
Section: Proposed Indicators For the Presence Of Viruses In Water Andmentioning
confidence: 99%
“…They can, however, accumulate viruses in their bodies at a level equal to that of the surrounding water. Thus, West Coast shore crabs were shown to acquire enteroviruses from artificially contaminated seawater and by feeding on contaminated mussels (2,3). Within 2 h after crabs were placed in virus-contaminated seawater, poliovirus was present in all parts of blue crabs, Callinectes sapidus (9).…”
mentioning
confidence: 99%